The effect of flipped learning strategy on positive thinking and learning the football suppression skill for students (Journal of Humanities and Social Sciences Research, 2023)
By emphasizing the use of a contemporary and diversified educational approach represented by the reverse learning strategy, one of the techniques that aid in acquiring skills quickly and saves time. In addition to taking into consideration students' unique peculiarities, which makes the lesson more fascinating, exciting, and enthusiastic via the use of an educational program to promote positive thinking and teach the art of throwing out football to students. The study aims to construct a positive thinking measure and to determine the influence of the flipped learning technique on fostering positive thinking and acquiring the ability of football suppression for students. The researchers employed the experimental technique with two equal groups (experimental and control), and the research sample population was defined as (96) first-year students in the College of Physical Education and Sports Sciences at Dhi Qar University for the academic year (2021-2022). The sample for creating the positive thinking scale consisted of (60) students, whereas the sample for the main experiment was picked at random and consisted of (30) students divided evenly into two experimental and control groups, each with (15) individuals. The positive thought scale was constructed using (24) elements from the building sample and then applied to the full sample and the suppression test in football in the pre and post-test. The instructional units were used in conjunction with the flipped learning technique for four weeks. It consisted of eight instructional units, with two educational units every week for two days (Tuesday and Thursday). One of the study's most notable findings was that the flipped learning technique led to the development of positive thinking and the level of student performance in the football suppression skill. The inverted learning strategy helped to understand and consolidate the information related to football suppression skills. Among the most important recommendations recommended by the researchers is the need to use the flipped learning strategy to develop positive thinking and raise the level of skill performance in football for students and the need to encourage teachers to use and adopt the flipped learning strategy in teaching various subjects.